Factors Associated with Exclusive Breastfeeding among Mothers who Work at Home at Tabanan Regency - Hesteria Friska Armynia Subratha; I Wayan Gede Artawan Eka Putra; Dyah Pradnyaparamita Duarsa (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: Working mothers and mothers who leave their babies in their home for more than 8 hours a day almost do not exclusively breastfeed their babies. The aim of this study was to determine the proportion of exclusive breastfeeding among mothers who work at home and factors associated with it. Methods: Cross-sectional survey was conducted by convenience sampling of 132 mothers with 6-12 months babies at Puskesmas Marga I Tabanan Regency from March-April 2016. The data was collected by interview about social-demographic characteristic,knowledge, perception, pregnancy and maternity counseling, early breastfeeding initiation, families support, medical assistant and exclusive breastfeeding. The data analyzed by univariate, bivariate, multivariate using STATA 12.1. Chi square applied in bivariate analysis and poison regression applied in multivariate analysis. Results: Proportion of respondents who exclusively breastfeed their babies for 6 months was 66.67%. Reasons for not exclusively breastfeed were not enough breastmilk (32.58%), no breastmilk (13.64%), families suggestion (8.33%), babies refused breastmilk (6.06%), health provider suggestion (2.27%) and to avoid the shape change of the breast (1.52%). Multivariate analysis found that variables associated with the exclusive breastfeeding were parity (APR=1.50; 95%CI: 1.01-2.15), early breasfeeding initiation (APR=1.80; 95%CI: 1.13-2.90) and families support (APR=1.4; 95%CI: 1.10-1.76). Conclusion: Factors significantly associated with exclusive breastfeeding were parities less than 3, early breasfeeding initiation and families support.